The role of age‐related T‐cell differentiation in patients with renal replacement therapy. Issue 10 (15th August 2017) - Schaier, Matthias; Leick, Angele; Uhlmann, Lorenz; Kälble, Florian; Eckstein, Volker; Ho, Anthony; Meuer, Stefan; Mahnke, Karsten; Sommerer, Claudia; Zeier, Martin; Steinborn, Andrea
Abstract : Dialysis patients have deficiencies regarding the generation of immune responses and show an increased susceptibility for infections. Persisting uremic conditions are made responsible for the increased aging of their immune system. In this study, we analyzed whether age‐related differences in the differentiation of both recent‐thymic‐emigrant‐(RTE)‐regulatory (Tregs) and RTE‐responder T cells (Tresps) into CD31 − ‐memory Tregs/Tresps led to differences in the suppressive activity of naive and memory Tregs on autologous Tresps between healthy volunteers and dialysis patients. We found that regardless of age, the differentiation of RTE‐Treg/Tresps into CD31 − ‐memory‐Treg/Tresps was significantly increased in dialysis patients. By analyzing the age‐related differences in the differentiation of Tregs/Tresps, we saw that in healthy volunteers RTE‐Tregs differentiate via CD31 + ‐memory Tregs into CD31 − ‐memory Tregs, which may strengthen the suppressive activity of the total Treg pool. In contrast RTE‐Tresps of healthy volunteers differentiate via mature naive (MN)‐Tresps into CD31 − ‐memory‐Tresps, which may weaken the reactivity of the total Tresp pool. Our data revealed that this normal differentiation via MN‐Tresps was lost in dialysis patients, suggesting that their Tresps are less sensitive to Treg‐mediated immunosuppression. Functional analysis of Tregs on autologous Tresps showed an increasing suppressive activity with age in healthy individuals, who therefore may have a lower risk of developing autoimmune diseases but owing to decreased reactivity of their Tresps are more likely to suffer from infections. In contrast, dialysis patients exhibited a decreasing suppressive activity with age, owing to strengthened Tresp reactivity, which could explain the higher prevalence of chronic inflammatory conditions in these patients.